2010
DOI: 10.3892/ijmm_00000508
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an intermediate signature that marks the initial phases of the colorectal adenoma-carcinoma transition

Abstract: Abstract. The colorectal adenoma-carcinoma sequence describes the stepwise progression from normal to dysplastic epithelium and then to carcinoma. Only a small proportion of colorectal adenomas (CRAs) progress to colorectal carcinomas (CRCs). Endoscopic intervention is currently being used on patients with high grade dysplasia CRAs, with diameters of >1 cm, or villous components of >25% who are at higher risk than other CRA sufferers. During the process, biopsy samples are taken for conventional histological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…Angiogenesis and macrophage recruitment are closely related to cancer progression, and these two biological processes share common pathways (39). In this study, we found that FOXQ1 inhibition in CRC cells results in suppressed proliferation and migration of CRC cells in vitro (Figure 2), this result was consistent with ours (12) and other previous reports in CRC (11,21). Furthermore, the impact of FoxQ1 on promoting tumor cell proliferation was also well established in other solid tumors including ovarian cancer (16), neuroblastoma (20), lung cancer (22), gastric cancer (23), and liver cancer (40).…”
Section: Foxq1 Expression Is Positively Correlated With Twist1 and CCsupporting
confidence: 91%
See 3 more Smart Citations
“…Angiogenesis and macrophage recruitment are closely related to cancer progression, and these two biological processes share common pathways (39). In this study, we found that FOXQ1 inhibition in CRC cells results in suppressed proliferation and migration of CRC cells in vitro (Figure 2), this result was consistent with ours (12) and other previous reports in CRC (11,21). Furthermore, the impact of FoxQ1 on promoting tumor cell proliferation was also well established in other solid tumors including ovarian cancer (16), neuroblastoma (20), lung cancer (22), gastric cancer (23), and liver cancer (40).…”
Section: Foxq1 Expression Is Positively Correlated With Twist1 and CCsupporting
confidence: 91%
“…IHC results showed that FOXQ1, Twist1, and CCL2 each were significantly upregulated in CRC tissues compared with adjacent nontumorous tissues, and that CD31 and CD68 were moderately upregulated ( Figure 7A). Furthermore, the overexpression of FOXQ1 was significantly correlated with lymph node metastasis or higher TNM stage (Table 1), which is consistent with our previous study (12). Further analysis verified the statistically significant correlation between FOXQ1 and Twist1 (P<0.01) ( Table 2).…”
Section: Foxq1 Expression Is Positively Correlated With Twist1 and CCsupporting
confidence: 90%
See 2 more Smart Citations
“…Homozygous deletion of Foxq1 was associated with impaired gastric function and increased embryonic lethality [64,65]. Then, it became evident that overexpression of FOXQ1 is common in colorectal adenocarcinoma and associated with tumour growth and metastasis [45,66,67] (Figure 1.4). Later, FOXQ1 was described as putative oncogene in many human cancers, where it is generally associated with poor prognosis [68][69][70].…”
Section: Forkhead Box Q1mentioning
confidence: 99%